Plant Growth, Fruit Production and Total Terpenoid Compounds in Bitter Gourd (Momordica charantia L.) at Various Levels of Phosphorus Fertilization - Rizva, Dian Novira; Melati, Maya; Aziz, Sandra Arifin (Department of Agronomy and Horticulture, IPB University, 2024)
Bitter gourd (Momordica charantia L.) fruits have been reported to have pharmacological functions such as anti-bacterial, lowering blood sugar, and preventing cardiovascular disease. Terpenoids are the bioactive compounds that play a role in those functions. The phosphorus is essential in the biosynthesis of terpenoids. This research aimed to determine plant growth characteristics, fruit production, and terpenoid production in bitter gourds fertilized with various phosphorus. The experiment was conducted at the IPB experimental station in Cikarawang, 6o32’58.3” S south latitude and 106o43’54.8” E east longitude, Bogor, Indonesia, from July to October 2023. The experiment used a completely randomized block design with a single factor: fertilizer treatments and three replications. The treatments were without fertilizer, chicken manure only, and varying dosages of SP-36 (0, 20, 40, 60 g per plant). Plants treated with 40 g SP-36 per plant significantly had longer stems at four weeks after planting (WAP) (153.5 cm), substantially more female flowers at 5 WAP (6.4 flowers), heavier fresh weight per fruit (243.98 g), and higher fruit carotene level (86 μg.g-1). Plants treated with 60 g SP-36 per plant had the heaviest fresh fruit weight per plant (2,820.9 g). On the other hand, chicken manure fertilizer resulted in an elevated number of female flowers at 7 WAP (6.8 flowers), leaf potassium content (3.41%), chlorophyll a (250 μg.g-1), chlorophyll b (114 μg.g-1), and total chlorophyll concentration (363 μg.g-1). There were no significant differences in IC50, terpenoid content, and terpenoid production; however, plants treated with 60 g SP-36 per plant tended to have lower IC50 (1,347.67 ppm) and terpenoid content (95,227 μmol NE.g-1 dry fruit). In contrast, plants treated with 40 g SP-36 per plant tended to have higher terpenoid production (15,995 mmol NE per plant) than other treatments.